Pemikiran Filsafat Etik Immanuel Kant dan Relevansinya dengan Akhlak Islam - Achmad, Ghufran Hasyim (Lembaga Yasin AlSys, 2022)
Many philosophers have discussed ethics. Ethics as something that cannot be separated in human life, one of which is Immanuel Kant's Ethics. Kantian ethics is an ethics of obligation that does not require happiness or external factors. This is also in line with Islam that commendable morals lead humans to the highest happiness, namely the reality of God. Islam teaches morals called Islamic morals which are based on the Qur'an and hadith. Research objectives: 1) Biography, 2) Immanuel Kant's philosophy, 3) Immanuel Kant's ethical relevance to Islamic morals. The research method used is library research with a descriptive approach. Research result; 1) Immanuel Kant was born on April 22, 1724 in Konigsberg, East Prussia. Heone of the German thinkers. Regarding ethics Immanuel Kant wrote at least three books, first; Fundations of Metaphysics of Morals, second; Critique of Practical Reason, third: Metaphysics of Ethics. 2) Kant's ethical philosophy, including the ethical philosophy of deontology. Kant's ethical rationale, among others; Categorical immersion, legality and morality, autonomy of will, goodness and happiness, ethics and religion.3) Immanuel Kant's ethical relevance to Islamic morality, among others; a) The basis of obligation, b) Freedom, c) The ultimate goal.